Opowieść rodzi się w dialogu — specyfika narracji w reportażu radiowym - Sygizman, Kinga (Zagadnienia Rodzajów Literackich, 2022)
The article is an attempt to discuss the specificity of the narrative in radio documentary. The documentary is treated as an artistic form of radio based on the character’s statement born during a meeting with a reporter, the documentary maker. The narrative is treated as an individual statement by the character, but also as a text of culture. Dialogue rules both perspectives. The relationship takes place between the character and the reporter, but also between subsequent elements of the audio material composed according to the author’s intention. We also discuss about the radio documentary being as a form of dialogue with the listener. The essence of the article is the proposed divisions of the radio reportage narrative, taking into account the narrative as a personal statement and as a text. The categorization was supported by examples from Polish radio documentaries. Theoretical considerations are based on studies on artistic radio genres, psychological narrative, narrative identity, and the philosophy of encounter. Radio documentary, which is emphasized by theoreticians and practitioners of the genre, is born out of a situation where there is a dialogical meeting between the author and the protagonist, and the verbalization of experiences during this meeting is a form of identity building. A look at radio documentary from a psychological perspective and the resulting classifications will indicate the importance of interdisciplinary research into audio artistic genres.